The Role of Foreign Direct Investment in the Socio-Economic Development of the Country - Khoshimov Sabir Murtazaevich (Global Scientific Publishing, 2023)
The article discusses the economic nature and importance of foreign direct investment, the role and importance of foreign direct investment in the socioeconomic development of the country, existing problems, analytical data, conclusions, proposals and recommendations for solving them
Keywords: investment attractiveness; foreign direct investment; investment climate; investment policy